2004
DOI: 10.1111/j.1523-1755.2004.00793.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine gene expression profiles in kidney medulla and cortex of obese hypertensive dogs

Abstract: A high fat diet in dogs is associated with marked changes in renal gene expression profiles that provide potential molecular links to pathways associated with altered renal function and structure in obesity hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 47 publications
0
8
0
3
Order By: Relevance
“…Postprandial hyperchylomicronemia and hypercomplementemia near adipose tissue would activate the complement pathway and accelerate C3 tick-over, resulting in overproduction of ASP in obese patients with increased amounts of adipose tissue, and hyperinsulinemia in patients with insulin-resistant type 2 diabetes mellitus. Hyperproduction of ASP induced by chylomicron would promote excess complement activation in organs other than adipose tissue, as well as the mRNA expression of genes associated with metabolic syndrome (48). Hyperproduction of ASP may increase the risk of metabolic syndrome and diabetic complications.…”
Section: Discussionmentioning
confidence: 99%
“…Postprandial hyperchylomicronemia and hypercomplementemia near adipose tissue would activate the complement pathway and accelerate C3 tick-over, resulting in overproduction of ASP in obese patients with increased amounts of adipose tissue, and hyperinsulinemia in patients with insulin-resistant type 2 diabetes mellitus. Hyperproduction of ASP induced by chylomicron would promote excess complement activation in organs other than adipose tissue, as well as the mRNA expression of genes associated with metabolic syndrome (48). Hyperproduction of ASP may increase the risk of metabolic syndrome and diabetic complications.…”
Section: Discussionmentioning
confidence: 99%
“…An experimental study in dogs showed that a high-fat diet causes obesity, increased arterial pressure, hyperinsulinemia, activation of the renin-angiotensin system, glomerular hyperfiltration, and structural changes in the kidney (27). A high-fat diet in dogs is also associated with marked changes in renal cytokine gene expression profiles (28).…”
Section: Discussionmentioning
confidence: 99%
“…High-fat feeding dogs (supplementing standard food with an additional 0.5-0.9 kg of cooked beef fat/day) for 10 wk led to significantly increased kidney and total body weight, mean arterial blood pressure, and heart rate, accompanied by induction of TGF-␤1 and other proinflammatory cytokines and profibrotic factors in the medullary interstitium, along with enhanced glomerular filtration rate and higher renal plasma flow (63). Moreover, plasma renin was significantly elevated in high fat-fed dogs, supporting the evidence for an activation of the RAAS by the Western-style diet.…”
Section: A High-fat Diet As a Risk Factor For Ckdmentioning
confidence: 99%